2004
DOI: 10.1002/pssb.200304622
|View full text |Cite
|
Sign up to set email alerts
|

Formability and thermal stability of α′ phase in (Fe1−y Coy)–(B, C, N) films

Abstract: In order to find a way to obtain stable α′′-Fe 16 X 2 phase, the formability and thermal stability of α′ (bct) phase were discussed. According to a rigid sphere model, we concluded that the less formability of B for the α′ phase is due to its large atomic radius. We elucidated the difference of thermal stability of α′-Fe -X, taking into account their decomposition process. While, the decomposition of α′-Fe -N progresses only by the migration of N, without changing the bone structure of Fe lattice, the addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…For instance, Fe 16 N 2 was reported as a tetragonal compound with c/a = 1.1 and K u = 0.45 × 10 6 J·m −3 29 . In FeCo-based alloys, (Fe y Co 1−y )−(B, C, N) (y ≥ 0.7) films with t = 300 nm deposited on MgO substrates have been studied, and a tetragonal structure resembling that of Fe 16 N 2 was detected in the Fe-rich regions 29,30 . The (Fe 0.4 Co 0.6 ) 98 C 2 films with t = 100 nm deposited on AuCu buffer layers were characterised by c/a = 1.03 and K u = 0.44 × 10 6 J·m −3 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Fe 16 N 2 was reported as a tetragonal compound with c/a = 1.1 and K u = 0.45 × 10 6 J·m −3 29 . In FeCo-based alloys, (Fe y Co 1−y )−(B, C, N) (y ≥ 0.7) films with t = 300 nm deposited on MgO substrates have been studied, and a tetragonal structure resembling that of Fe 16 N 2 was detected in the Fe-rich regions 29,30 . The (Fe 0.4 Co 0.6 ) 98 C 2 films with t = 100 nm deposited on AuCu buffer layers were characterised by c/a = 1.03 and K u = 0.44 × 10 6 J·m −3 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…To consider the structural stability of the (Fe 0.4 Co 0.6 ) 0.9 V 0. [19,31]. The ΔH value of Fe 16 C indicates that it is formable at low temperatures.…”
Section: Enthalpy Of Formation (δH) Evaluated By Dft Calcul Ations An...mentioning
confidence: 99%
“…MgO substrates [18,19]. They found that the Fe-rich alloys showed a tetragonal structure, which became unstable with an increase in the Co content.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, soft magnetic properties can be induced with the help of C, that is, the measured magnetic properties change from hard to soft in Fe-C-N compounds. [13][14][15][16][17] These results imply that light elements play an important role in tailoring the electronic states of neighboring magnetic elements.…”
Section: Introductionmentioning
confidence: 99%